2021
DOI: 10.1186/s12933-021-01405-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prediabetes and diabetes on 3-year outcome of patients treated with new-generation drug-eluting stents in two large-scale randomized clinical trials

Abstract: Background Diabetes is associated with adverse outcomes after percutaneous coronary intervention with drug-eluting stents (DES), but for prediabetes this association has not been definitely established. Furthermore, in patients with prediabetes treated with contemporary stents, bleeding data are lacking. We assessed 3-year ischemic and bleeding outcomes following treatment with new-generation DES in patients with prediabetes and diabetes as compared to normoglycemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It has been demonstrated that CAD in the DM population was more likely to be diffuse disease and multivessel disease [ 24 ], and was associated with more significant plaque burden and lipid-rich plaque, prone to rupture [ 2 ], which lead to a procedural complexity in reperfusion therapy. DM is also associated with adverse stent-related outcomes after PCI, increasing the risk of stent restenosis or thrombotic obstructions [ 4 7 ]. A pooled analysis of BIO-RESOR and BIONYX trials demonstrated that patients with DM had higher risks of target lesion failure than patients without DM after PCI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that CAD in the DM population was more likely to be diffuse disease and multivessel disease [ 24 ], and was associated with more significant plaque burden and lipid-rich plaque, prone to rupture [ 2 ], which lead to a procedural complexity in reperfusion therapy. DM is also associated with adverse stent-related outcomes after PCI, increasing the risk of stent restenosis or thrombotic obstructions [ 4 7 ]. A pooled analysis of BIO-RESOR and BIONYX trials demonstrated that patients with DM had higher risks of target lesion failure than patients without DM after PCI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM is also associated with adverse stent-related outcomes after PCI, increasing the risk of stent restenosis or thrombotic obstructions [ 4 7 ]. A pooled analysis of BIO-RESOR and BIONYX trials demonstrated that patients with DM had higher risks of target lesion failure than patients without DM after PCI [ 7 ]. Furthermore, a recent study by Kim et al reported a greater plaque progression in the DM population using serial coronary computed tomographic angiography data [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that after treatment with new-generation drug-eluting stents, both patient groups had higher risks of ischemic and bleeding events compared with non-DM patients. Differences in major bleeding were mainly attributable to dissimilarities in baseline characteristics [ 19 ] .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was based on patients with diabetes mellitus, however, not only patients with diabetes mellitus but, patients with pre-diabetes were at a higher risk for ischemic events following newer generation stents implantation. This was shown in a post-hoc analysis whereby data from the BIO-RESORT and BIONYX stent trials were pooled for study analysis [ 21 ]. In addition, when second generation DES were compared with first generation DES, stent related adverse events were significantly lower with the second generation DES, however, it was observed that the use of dual antiplatelet therapy beyond one year did not reduce late stent thrombosis among patients who were revascularized with second generation DES, but late stent thrombosis was reduced in patients who were implanted with first generation DES [ 22 ].…”
Section: Discussionmentioning
confidence: 99%